Komunikasi Islam Dalam Membentuk Konsep Diri Murid Penyandang Tunanetra - Deni Yanuar; Nur Anisah; Mini Sartika (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This research aims to find out how Islamic communication is shaping the concept of students who are visually impaired. The approach used in this study uses qualitative descriptive methods. The research was conducted on SLB Bukesra Banda ACEH with the informant is 4 people, among them 2 teachers who teach the blind students, and 2 students who are visually impaired. The data collection techniques used are observations and interviews. The symbolic interaction theory is used in this study. The results showed that Islamic communication through interpersonal approaches was very influential to form the concept of self-blind pupils and from research researchers also found that unknowingly to To conduct interpersonal communication teachers to the students who are blind using effective communication features that are openness, empathy, support, positive sense, and similarity. In addition, the gifts given by the teacher become one of the supporting factors in intrepersonal communication, although they have fewer obstacles when the blind students are being sensitive but overall interpersonal communication Teacher with the blind students in SLB BUKESRA Banda Aceh went smoothly and successfully.